1994
DOI: 10.1093/infdis/170.5.1057
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis Of Toxoplasmic Encephalitis

Abstract: The incidence of toxoplasmic encephalitis (TE) has increased with the increasing numbers of patients with immunodeficiencies, in whom reactivation of latent Toxoplasma infection may occur. This highlights the important role of the immune response in maintaining infection with Toxoplasma gondii in a latent form. Because the brain is the most commonly affected site of latent infection and because it is anatomically unique in regard to the immune system, understanding the systemic immune response to infection wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 70 publications
2
74
0
Order By: Relevance
“…Silveria et al (2001) showed that ocular toxoplasmosis is due to acute infection after birth because the rate of infection in young children was low. Although, postnatally acquired infections were reported to be asymptomatic, manifestations of toxoplasmosis include large lymph nodes (particularly of the cervical region) headaches, muscles aches and sore throat (Hunter and Remington, 1994). Subclinical forms of toxoplasmosis have also been observed in children at birth, without higher incidence of prematurity or low weight at birth.…”
Section: Toxoplasma Gondii Genotypes and Pathologymentioning
confidence: 99%
“…Silveria et al (2001) showed that ocular toxoplasmosis is due to acute infection after birth because the rate of infection in young children was low. Although, postnatally acquired infections were reported to be asymptomatic, manifestations of toxoplasmosis include large lymph nodes (particularly of the cervical region) headaches, muscles aches and sore throat (Hunter and Remington, 1994). Subclinical forms of toxoplasmosis have also been observed in children at birth, without higher incidence of prematurity or low weight at birth.…”
Section: Toxoplasma Gondii Genotypes and Pathologymentioning
confidence: 99%
“…Toxoplasmosis is a potentially fatal disease of the developing human fetus and immunocompromised (e.g., AIDS and transplant) patients and can cause severe ocular disease in otherwise healthy individuals (7,10,14). Recent population genetic studies have identified a remarkably limited number of Toxoplasma gondii genotypes in nature, the vast majority of which fall into one of only three distinct lineages (9).…”
mentioning
confidence: 99%
“…From there tachyzoites disseminate throughout the body and reach immunologically protected sites including brain, retina and fetus. [7][8][9] Latent infection with T. gondii involves an elaborate interplay between the parasite and the host in which the parasite ensures its survival and proliferation but avoids fatal damage to the host at the same time. 10 By definition, latent infections involve a complex interplay between parasite and host, producing some degree of harmony.…”
Section: Discussionmentioning
confidence: 99%